1982
DOI: 10.1111/j.1365-2362.1982.tb02238.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes after arterial reconstruction in the forefoot local vasoconstrictor response to increased venous transmural pressure

Abstract: Local blood flow regulation on the forefoot was studied by the 133Xe wash-out technique in twenty-seven patients before and after arterial reconstruction for occlusive arterial disease. In thirteen limbs with severe symptoms the local vasoconstrictor response to increased venous pressure was absent preoperatively, as blood flow in the foot increased in median by 47% when the foot was lowered 40 cm below the heart. Three months postoperatively the vasoconstrictor response had returned as blood flow decreased 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The normal vasoconstrictor response on rising from the supine to the sitting position is diminished in patients with mild arterial disease [1] and is either absent or there is a paradoxical rise in skin perfusion in CLI [2]. More recently, studies by Jacobs et al [3] using capillary microscopy and transcutaneous oximetry have shown that the microcirculation is severely compromised in CLI with a reduced capillary density and capillary dilation.…”
Section: Introductionmentioning
confidence: 96%
“…The normal vasoconstrictor response on rising from the supine to the sitting position is diminished in patients with mild arterial disease [1] and is either absent or there is a paradoxical rise in skin perfusion in CLI [2]. More recently, studies by Jacobs et al [3] using capillary microscopy and transcutaneous oximetry have shown that the microcirculation is severely compromised in CLI with a reduced capillary density and capillary dilation.…”
Section: Introductionmentioning
confidence: 96%
“…The normal vasoconstrictor response on rising from the supine to the sitting position is diminished in patients with mild arterial disease [1] and is either absent or there is a paradoxical rise in skin perfusion in CLI [2]. The normal vasoconstrictor response on rising from the supine to the sitting position is diminished in patients with mild arterial disease [1] and is either absent or there is a paradoxical rise in skin perfusion in CLI [2].…”
Section: Introductionmentioning
confidence: 99%
“…Autoregulation mechanisms do maintain a constant perfusion pressure in the limbs, although this mechanism fails in patients with severe PAD. An increase in the arteriovenous pressure gradient may cause an increase in microvascular permeability for fluids and proteins [5, 9] and inflammatory responses following revascularization, resulting in edema [10, 34]. However, the attribution of hyperemia is probably limited, as illustrated by the occurrence of only a small increase in limb volume following percutaneous revascularization because no lymphatics are damaged [35].…”
Section: Discussionmentioning
confidence: 99%
“…Also, edema is known to impair macrovascular and microvascular circulation [7]. The pathophysiology of postreconstruction edema is thought to be a combination of hyperemia [8][9][10][11], increased capillary permeability [7,12], and lymphatic [3,4,[13][14][15][16] and venous [4,17] disruption. Reperfusion of ischemic tissue leads to up-regulation of inflammatory processes as well [18,19].…”
Section: Introductionmentioning
confidence: 99%